Pollution in a promised land : an environmental history of Israel - Tal, Alon, 1960- (Berkeley, Calif. : University of California Press, 2002)
Virtually undeveloped one hundred years ago, Israel, the promised "land of milk and honey," is in ecological disarray. In this gripping book, Alon Tal provides--for the first time ever--a history of environmentalism in Israel, interviewing hundreds of experts and activists who have made it their mission to keep the country's remarkable development sustainable amid a century of political and cultural turmoil
The pathology of a polluted river: an introduction to Israel's environmental crises -- Reclaiming a homeland: Zionism's mixed ecological message -- Palestine's environment, 1900-1949: prelude to disaster or benign half-century? -- The forest's many shades of green -- The emergence of an Israeli environmental movement -- A general launches a war for wildlife -- The quantity and quality of Israel's water resources -- Israel's urban environment, 1948-1988: the politics of neglect -- A ministry of the environment comes of age -- Israel, Arabs, and the environment -- Environmental activism hits its stride -- Toward a sustainable future?
Includes bibliographical references (pages 435-516) and index.
Print version record.
English.
JSTOR
Keywords: Pollution -- Israel; Israel -- Environmental conditions; Environmental protection -- Israel; Environmental policy -- Israel; Pollution -- Israël.; Environnement -- Protection -- Israël.; Environnement -- Politique gouvernementale -- Israël.; SCIENCE -- Environmental Science (see also Chemistry -- Environmental); POLITICAL SCIENCE -- Public Policy -- Environmental Policy; NATURE -- Environmental Conservation & Protection; Ecology; Environmental policy; Environmental protection; Pollution; Israel